Determinacion de hierro serico, hematocrito y hemoglobina como ayuda de diagnostico en anemia ferropenica en mujeres embarazadas atendidas en el hospital andino alternativo de chimborazo durante el periodo enero a junio del 2011. - Guanga, Blanca (2011)
The following investigation has as objective to determine the importance of the analysis of the tests of Iron Serco, hematocrito, hemoglobin in the early diagnosis of Anemia for Deficiency of Iron Sérico in patient that you/they agree since to the prenatal control to Hospital Andino Alternative of Chimborazo these tests is of importance for the pursuit of the illness of anemia for iron lack being this fundamental element in the alive being's life but especially of the woman in state gestacional, since its deficiency can cause problems in the fetal development.